Excitatory GABA: How a Correct Observation May Turn Out to be an Experimental Artifact - Bregestovski, Piotr; Bernard, Christophe (Frontiers in Pharmacology, 2012)
The concept of the excitatory action of GABA during early development is based on data obtained mainly in brain slice recordings. However, in vivo measurements as well as observations made in intact hippocampal preparations indicate that GABA is in fact inhibitory in rodents at early neonatal stages. The apparent excitatory action of GABA seems to stem from cellular injury due to the slicing procedure, which leads to accumulation of intracellular Cl− in injured neurons. This procedural artifact was shown to be attenuated through various manipulations such as addition of energy substrates more relevant to the in vivo situation. These observations question the very concept of excitatory GABA in immature neuronal networks.